ExerStart: helping seniors be active and independent for less. Issue 2 (8th April 2019) - van Esch, Patrick; Duffy, Sarah Maree; Teufel, James; Northey, Gavin; Elder, Edward; Frethey-Bentham, Catherine; Cook, Thomas B.; Heller, Jonas
Abstract : Purpose: The purpose of this research is to examine a downstream social marketing program that slows the typical decline in functional fitness and independence of adults over 55 with particular attention to the ROI and the efficiency of the program. Design/methodology/approach: Within subjects quasi-experimental design. Findings: The ExerStart program is cost-efficient and effective delivering an ROI of 33 per cent. The participants of the ExerStart social marketing program significantly improved functional fitness. Further, this program demonstrates that this result may be achieved with just four exercises rather than six. Practical implications: A successful, cost-effective, high-retention social marketing program is outlined for social marketers who aim to increase the functional fitness and independence of adults over 55 years. Social implications: Two societal benefits, the first is that it provides direction about how to efficiently prolong the independence of adults over 55 years, and the second is that it decreases pressure and costs on the healthcare system. This may be useful for policy makers and social marketers alike. Originality/value: The authors contribute to the literature in two important ways. First, this paper details a cost-effective intervention that improves the physical fitness of a significant and growing portion of the community and suggests additional considerations for future ROI calculations. Second, this paper contributes methodologically by introducing the senior fitness test (a new criterion-referenced clinically relevant physical fitness standard specifically developed for seniors).